Advantages of using nested collision induced dissociation/post-source decay with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry: Sequencing of novel peptides from wasp venom - Hisada, Miki; Konno, Katsuhiro [UNESP]; Itagaki, Yasuhiro; Naoki, Hideo; Nakajima, Terumi (My University, 2000)
We have examined the applicability of the 'nested' collision induced dissociation/post-source decay (CID/PSD) method to the sequencing of novel peptides from solitary wasps which have neurotoxic venom for paralyzing other insects. The CID/PSD spectrum of a ladder peptide derived from an exopeptidase digest was compared with that of the intact peptide. The mass peaks observed only in the CID/PSD spectrum of a ladder peptide were extracted as C-terminal fragment ions. Assignment of C-terminal fragment ions enabled calculation of N-terminal fragment masses, leading to differentiation between N-terminal fragment ions and internal fragment ions. This methodology allowed rapid and sensitive identification by removing ambiguity in the assignment of the fragment ions, and proved useful for sequencing unknown peptides, in particular those available as natural products with a limited supply. Copyright (C) 2000 John Wiley and Sons, Ltd.